Annotating opinion—evaluation of blogs: the Blogoscopy corpus - Daille, Béatrice; Dubreil, Estelle; Monceaux, Laura; Vernier, Matthieu (Language Resources and Evaluation, 2011)
The blog phenomenon is universal. Blogs are characterized by their evaluative use, in that they enable Internet users to express their opinion on a given subject. From this point of view, they are an ideal resource for the constitution of an annotated sentiment analysis corpus, crossing the subject and the opinion expressed on this subject. This paper presents the Blogoscopy corpus for the French language which was built up with personal thematic blogs. The annotation was governed by three principles: theoretical, as opinion is grounded in a linguistic theory of evaluation, practical, as every opinion is linked to an object, and methodological as annotation rules and successive phases are defined to ensure quality and thoroughness.